Computational and experimental determination of energy loss of the operating fluid in the intake system of the automobile piston pneumatic engine using the exergy method - Voronkov, A.; Charchenko, A.; Nikitchenko, I.; Novikova, Ye.; Teslenko, E.; Nazarov, A.; Воронков, О. І.; Харченко, А. І.; Нікітченко, І. М.; Новикова, Є. Б.; Тесленко, Е. В.; Назаров, А. О.; et al. (Харьковский национальный автомобильно-дорожный университет, 2018)
The application exergy method of the thermodynamic analysis for determining the energy loss of the operating fluid in the intake system of the automobile piston pneumatic engine using experimental data of its engine test rigs has been considered. The analysis of the performed exergy calculational and experimental research on the evaluation of energy loss in the intake system of the engine for current modes of its operation has been presented. The sample of a piston pneumatic engine for a combined automobile power unit created at the ICE Department of KhNAHU requires further improving and developing especially such components and systems as those connected to the burn process. A compressed air intake system is one of them. Compressed air is not only some working fluid for a pneumatic engine but the energy source for its intake system. The energy loss factor like reliability and durability is referred to the performance and efficiency factors. The object of the study is a pneumatic engine created by converting a gasoline four-cylinder four-stroke ICE at the ICE Department of KhNAHU. The experimental research was carried out by laboratory engine test rigs of the pneumatic engine with speed characterization provided that two thermodynamic parameters of compressed air at the intake were kept constant for each characteristic: pressure ps = idem and temperature Тs = 293 K. In each test mode all external parameters of the pneumatic engine were recorded and indicator diagrams of the first cylinder were taken. Each speed characteristic consisted of 6–8 modes ps= idem and Тs= 293 К = idem with changing the rotational rate of the crankshaft n, rpm, from minimally stable (about n=200 rpm) to maximum possible n = 1000 ± 50 rpm. It should be noted that there is an operating fluid pressure drop in the intake system chamber due to available inconvertibilities: throttling in the test port, hydraulic loss along the intake port as a result of fluid friction, swirls and other gas-dynamic phenomena. The exergy loss of the operating fluid enthalpy in the intake system Dвп=Евп-Енапwith the intake pressure рs = 0.5 MPais 13.3 kW, with the intake pressure рs = 0.7 MPa is 15.0 kW, with the intake pressure рs = 0.9 MPa is 16.9 kW, with the intake pressure рs = 1.1 MPa is 19.7 kW.
Розрахунково-експериментальне визначення втрат енергії робочого тіла в системі впуску автомобільного поршневого пневмодвигуна з використанням ексергетичного методу
Расчетно-экспериментальное определение потерь энергии рабочего тела в системе впуска автомобильного поршневого пневмодвигателя с использованием эксергетического метода
Keywords: piston pneumatic engine; intake system; energy loss; enthalpy exergy; maximum efficient power modes; поршневий пневмодвигун; система впуску; енергетичні втрати; ексергія ентальпії; режими максимальної ефективної потужності; поршневой пневмодвигатель; система впуска; энергетические потери; эксергия энтальпии; режимы максимальной эффективной мощности